COMPARISON OF CEMENT AUGMENTATION VS NON-AUGMENTED FRACTURE FIXATION OF INTERTROCHANTERIC FEMUR FRACTURE IN ELDERLY PATIENTS - BAKSHI, AMANDEEP SINGH; SINGH, JASPREET; ABHISHEK; SHARMA, MUKUL; SHARMA, MUDIT KUMAR; SHARMA, MUDIT KUMAR; SINGH, HARJAP; MEHTA, HARRY (International Journal of Current Pharmaceutical Research, 2025)
Objective: To compare the effectiveness of cement-augmented versus non-augmented fixation methods for treating intertrochanteric femur fractures. Methods: This prospective study was done in a tertiary care hospital of North India on patients presenting with intertrochanteric fractures. After enrolment, the patients using the stringent selection criteria they underwent fracture reduction with and without cement augmentation. Functional assessment utilising the Harris Hip Score (HHS), Quality of life assessment and associated complications were evaluated. Follow-up was done at 6 w, 3 mo, 6 mo and until radiographic union was achieved. Results: The mean duration of operation was significantly longer in Group I (59.68 min) compared to Group II (49.72 min; p<0.0001). Functional outcomes, assessed using HHS and Barthel index, showed non-significant differences between groups. However, intra-group analyses indicated significant improvements over time. Radiologically, Group II had a significantly greater mean sliding distance of the screw/blade (14.12 mm vs. 12.14 mm; p<0.00001) and higher mean varus deviation (7.16° vs. 3.15°; p<0.0001). Complications were minimal and similar in both groups, with no systemic or thromboembolic complications reported. Conclusion: The study found significant differences in operative time between the two groups, but functional outcomes were comparable at all follow-up intervals. Radiological analyses revealed significant differences in screw/blade sliding and varus deviation, indicating that cement augmentation may affect biomechanical stability.